General practice recruitment - a survey of awareness and influence of the Scottish Targeted Enhanced Recruitment Scheme (TERS). Issue 5 (3rd September 2019) - Lee, Kenneth; Cunningham, David E.
ABSTRACT: The World Health Organisation reported that health-care systems worldwide have problems with the recruitment and retention of general practitioners (GPs) into clinical practice, particularly to rural and under-served areas. A recent survey of United Kingdom (UK) trainees found that they valued posts with good training conditions, were in desirable locations and gave opportunities for their partner. The Scottish Government has set a target to increase the number of GPs in Scotland by 800 in the next 10 years. In recent years, GP speciality training recruitment has been challenging with significant vacancies in some training programmes, primarily in rural areas, or urban areas with a history of poorer recruitment. Recruitment incentive schemes are in operation in different countries in the UK. The Scottish Government introduced a Targeted Enhanced Recruitment Scheme (TERS), offering a £20, 000 payment to GPST trainees accepting a targeted post. This study aimed to evaluate awareness and influence of the TERS initiative on programme choice in Scotland in August 2017. A survey was developed and sent to GP trainees taking up a GPST post in August 2017. Ninety-five out of 245 doctors responded (response rate of 39%). Almost two-thirds (65.3%) were aware of TERS at the time of application and this was via word of mouth and from the National Recruitment Office website. Only 21% of GPSTs aware of TERS were influenced by it in their choice of training location. The locations of family, spouse or partner, and of pre-existing geographical preferences were more influential than TERS.